EDUCATIONAL TECHNOLOGIES: MEMBERSHIP OF PHILOSOPHICAL LAW AND CATEGORIES IN SCIENTIFIC AND TECHNICAL CREATION - Mamasiddiq Tulanov (Journals Park Publishing, 2022)
The article provides a philosophical analysis of the theoretical and practical significance of philosophical laws and categories in scientific and technical creativity. It has been studied that there is a growing need for the achievements of modern science, scientific discoveries and creative thinking around the world.
Keywords: creativity; thinking; research